PENGARUH JUMLAH KREDIT DAN PEMINJAM TERHADAP STABILITAS SISTEM KEUANGAN PADA FINTECH PEER TO PEER LENDING TAHUN 2019 SAMPAI 2022 - Imam Safi'i; Faishal Fadli (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the effect of credit and the number of borrowers in Fintech P2PL services on financial system stability from 2019 to 2022. The source of research data comes from secondary data, which comes from fintech statistics found on the Financial Services Authority (OJK) website. The research uses a quantitative approach with time series data analysis using Ordinary Least Square (OLS). The results of the study show that Fintech credit has a positive but not significant effect on financial system stability. The number of borrowers in P2PL fintech services as a form of financial inclusion has a negative and significant impact on financial system stability. This study has the implication that short-term credit provided by fintech does not affect financial system stability, while the number of borrowers in P2PL fintech services causes a decrease in financial system stability so that increased financial inclusion must be accompanied by strong risk mitigation to maintain financial system stability.